Spatial pattern in aerosol insecticide deposition inside a flour mill - Campbell, James F.; Arthur, Frank H.; Zhu, Kun Yan (My University, 2014)
Aerosol insecticides are commonly used for management of stored-product pests inside food facilities, but the physical complexity of the interior of most food facilities may influence the dispersal and deposition of droplets and create spatial variation in dosage. The spatial pattern in aerosol deposition was evaluated inside a flour mill using a high density grid of bioassay insects. Three insecticides, Aerotech with NyGuard and Pyrocide 100 + Diacon II, both pyrethrin and insect growth regulator combinations, and Vap20, an organophosphate, were evaluated at normal (27°C) and high (40°C) target temperatures. Using a newly developed efficacy index, there was spatial pattern to aerosol deposition detected for the pyrethrin insecticides and the pattern differed between aerosols and temperatures. Walls and corners, especially behind the direction of application, were especially vulnerable to zones of lower efficacy, and open areas in center of the room tended to have the highest efficacy. The organophosphate insecticide provided complete efficacy at all bioassay dish locations, probably due in part to its vapor toxicity. Using boxes 1 m in depth and 5, 10, or 20 cm in height and open on only one end, it was shown that aerosol dispersal under horizontal surfaces could be impacted by gap height, aerosol, and temperature. These results show the potential for spatial variation in aerosol efficacy within a food facility and identify locations with the potential to receive a lower insecticide dosage. To increase overall efficacy, these locations may be targeted for additional interventions to provide more uniform pest population suppression.
Citation: Campbell, J., Arthur, F., & Zhu, K. (2014). Spatial Pattern in Aerosol Insecticide Deposition Inside a Flour Mill. Journal of Economic Entomology, 107(1), 440-454. https://doi.org/10.1603/EC13423
Keywords: Confused flour beetle; Flour mill; Aerosol; Spatial pattern; Dispersion